RESEARCH OF WORLD AND DOMESTIC EXPERIENCE IN THE USE OF TRADEMARKS (Development Service Industry Management, 2025)
The article explores the global and domestic experience of using trademarks as key objects of intellectual property in the food industry and hospitality sector. The authors highlight that trademarks, brand names, and brands play a crucial role in shaping consumer perception, enhancing competitiveness, and ensuring sustainable business development. The research emphasizes that trademarks not only perform the function of product identification but also form the basis of consumer trust and loyalty, which are particularly significant in the hospitality industry.The study provides a legal framework for the protection of trademarks in Ukraine, referencing the Law “On Protection of Rights to Marks for Goods and Services,” which defines their types, registration procedures, and the scope of intellectual property rights. The analysis shows that trademarks can be verbal, graphic, three-dimensional, sound, or color combinations, all of which allow enterprises to distinguish their goods and services from competitors. Special attention is given to the importance of international registration through WIPO to secure trademarks on global markets and protect businesses from unauthorized use.A SWOT analysis of trademarks in the food and hospitality industries demonstrates their strengths, such as consumer identification, trust, and competitive advantage; weaknesses, including high costs and lengthy registration processes; opportunities, such as globalization, digital marketing, and franchising; and threats, including intellectual property infringements, legal disputes, and shifting consumer preferences. Case studies of international brands like Hilton, Marriott, and McDonald’s, as well as Ukrainian enterprises such as Premier Hotels and Resorts, Reikartz/Optima Hotels & Resorts, and Dmitry Borysov’s restaurant group, illustrate the practical significance of branding and legal protection in achieving market success.The conclusions underline that trademarks and brand names serve as powerful tools for positioning and differentiating businesses in highly competitive industries. The article stresses the need for enhanced awareness of intellectual property rights among domestic producers and calls for the adoption of specialized legislation regulating brand names and branding practices in Ukraine. Ultimately, trademarks are recognized as intangible assets that contribute not only to consumer orientation but also to the long-term profitability and competitiveness of enterprises in the global market.
Keywords: intellectual property; trademark; brand name; brand; food industry; hospitality industry